An Exploratory Study On Motives And Use Of Electronic Resources By Graduate Students In Navi Mumbai - WAGHMODE, DR. MANISHA LAXMAN; SHAIKH, DR. ASMAT ARA; SHUKLA, DR. MANISHA (The journal of contemporary issues in business and government, 2021)
Today’s era is very well-known as the electronic era or technology era as technology is growing at a very fast pace and today’s invention is tomorrow's ancient like this situation we are observing. As many changes are happening daily in technology as well as in the information technology world. During COVID-19, we know the importance of online/electronic resources is like a very vital need in education, as it acts as a very important educational tool for acquiring knowledge. One can use online/e-resources as a technological tool which can be helpful in developing reading habits too. A variety of characters of e-resources are available online like e- journals, e-books, online archive’s such as DOAJ, Elsevier, J-Gate, ProQuest online databases, PDF Drives, MOOCs etc. are accessible online using electronic devices. Without wasting much time, money, everyone can take advantage of acquiring information worldwide. This paper explores the e-resource usage by graduate students considering demographic factors like age, gender and motives for e-resources usage. For this study data of 246 graduate students from various colleges from the Navi Mumbai region is collected and used for this study. The data analysis is done using descriptive statistics and chi square test. It is found that there is no significant difference between e-resource usage and gender. It is also found that there is an association between age and sources of getting e-resources.